Transformation by Holding Time - De Nooijer, Paul (The Netherlands; Filmmuseum, 1976)
The film and the arrangement of Polaroids produced during and documented by the film that stand as a framed piece. In the film we watch from the side as a photographer takes a series of fifteen pictures of the motionless woman before the camera, posting the still-developing Polaroids after each shot until they completely obscure the movie camera's lens. The process underscores de Nooijer's long standing interest in perception and framework, and the sharp teals and faded greens of the final pictures represent his tendency to use unrealistic color in the creation of his work.
No Dialogue
Verzio Film Festival Submission
Keywords: Experimental films